Rietveld refinements of SnO2 ceramic powders doped with ZnO, WO3, CoO, Nb2O5 and MoO3 - Carrió, J. A.G.; Masson, T. J.; Munhoz, A. H.; De Jesus, M. M. [UNESP]; Perazolli, L. [UNESP]; Coleto, U. [UNESP]; Gutierrez-Antonio, S. [UNESP]; Marques, R. F.C. [UNESP]; Paiva-Santos, C. O. [UNESP] (De Gruyter, 2007)
Polycrystalline materials of SnO2 doped with ZnO, WO 3, CoO, Nb2O5, and MoO3. were synthesized by solid state reaction. X-ray powder diffraction data were collected with Cu Kα radiation from a Rigaku-Rint 2000 rotating anode source. The structural and profile parameters were refined by the Rietveld method using GSAS [2]. The obtained residual parameters are R wp = 11,93% and RBragg = 4,19%. The refined profile parameters indicate no anisotropic crystallite microstrain. The refinement results and Fourier differences calculations indicate that the dopants do not occupy interstitial sites in the crystal structure of SnO2. © by Oldenbourg Wissenschaftsverlag.
Keywords: Rietveld; SnO2; Varistor